Penguatan Literasi Sains dan Kreativitas Guru Bimbingan Belajar melalui Inovasi Pembelajaran IPA SD di Kota Mataram - Suranti, Ni Made Yeni; Gunawan, Gunawan; Nisrina, Nina; Ibrahim, Ibrahim (Indonesian Publication Center, 2023)
Science learning in tutoring institutions still faces challenges in strengthening teachers’ scientific literacy and creativity, particularly in the use of learning media and the implementation of innovative instructional strategies. This community service program aims to enhance the scientific literacy and creativity of tutoring teachers through innovative science learning at the elementary school level. The implementation method employed a participatory approach consisting of needs analysis, training and workshops, assistance in learning implementation, and program evaluation. The training materials included concepts of scientific literacy, inquiry-based learning, the development of innovative learning media such as e-modules, simple experiments, and virtual laboratories, as well as creative instructional strategies that promote students’ critical thinking. The results indicated improvements in teachers’ understanding of scientific literacy, the quality of developed instructional materials, and creativity in teaching practices within tutoring classrooms. In addition, more contextual, interactive, and 21st-century skills-oriented science learning practices were established. Therefore, this community service program contributes to strengthening the pedagogical competence of tutoring teachers while supporting the sustainable improvement of elementary-level science learning quality in Mataram City.